Analysis of genetic polymorphism in genes encoding cathelicidins from Vietnam indigenous yellow cattle breeds - Tuoi Do, Thi; Ngoc Ta, Hong; Anh Tran, Thi Thuy; Lan Pham, Doan; Phuc Do, Thi; Nguyen Thi Hong, Van (Academia Journal of Biology, 2023)
Cathelicidins include antimicrobial peptides (AMPs) and are involved in the innate immune defense against infections in mammals. Polymorphisms in the DNA sequence of cathelicidin genes could be relevant to inherited variations of host innate immunity, adaptation, and pathogen resistance. This study aims to investigate the sequence polymorphism of cathelicidin genes including CATHL2 and CATHL4 from local indigenous yellow cattle breeds of Vietnam. Genomic DNA samples were extracted from 52 individuals collected from different cattle populations in Vietnam including Ha Giang, Thanh Hoa, Nghe An and Phu Yen. The CATHL2 and CATHL4 genes were amplified by PCR, following sequencing for identification of the single nucleotide polymorphisms (SNPs) and/or insertion-deletion (indel) DNA sequence variations. The copy number variations (CNVs) of the CATHL4 gene were determined by cloning, single strand conformation polymorphism (SSCP) and real-time PCR. The comparative analysis results showed that there are 13 SNPs detected in all sequences of CATHL2 gene including 9 SNPs in intron 2 and intron 3, and 4 missense substitutions in exon 1, 2, and 3. These SNPs do not affect the predicted tertiary structure of Bac5 encoded by this gene. For CATHL4, the results revealed 15 SNPs, 3 indels and 1 repeat variation as motif (TG)n(G)n/(AC)n(C)n. Among these variations, the deletion 46delC in exon 1 of CATHL4 was detected in a sample of the Ha Giang breed causing a truncated polypeptide as predicted. The average copy number of CATHL4 of Vietnam indigenous cattle breeds using GADPH as a reference gene showed in range from 2.53 to 2.89 copies.